(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article focuses on modern technologies used in silkworm (Bombyx mori) rearing for breeding purposes. It highlights recent advancements in sericulture, including controlled environmental conditions, automated feeding systems, disease prevention methods, and digital monitoring tools. These innovations contribute to improving silkworm survival rates, enhancing cocoon quality and productivity, and ensuring more efficient and accurate breeding processes. The study emphasizes the importance of integrating scientific and technological developments into traditional sericulture practices to achieve higher efficiency and better selection outcomes.